PERAN BRAND IMAGE MEMEDIASI ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP PURCHASE INTENTION (STUDI PADA CALON KONSUMEN KEDAI FORE COFFEE DI KOTA DENPASAR) - Prayoga, I Komang Wiramas; Kerti Yasa, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023DO - 10.24843/EEB.2023.v12.i12.p01, 2023)
The coffee industry is one of the industries that is competitive in its rivalry so that various strategies are implemented in order to maintain business existence in the market, one of which is the Fore Coffee company. This research aims to explain the role of brand image in mediating the effect of e-WOM on purchase intention of Fore Coffee products. This research was conducted on potential customers in Denpasar City who were aware but had never bought Fore Coffee products with a sample size of 120 respondents. Data collection through online surveys in the January 2023 period and then analyzed using path analysis and sobel test with the help of the SPSS program. The results showed that e-WOM and brand image have a positive and significant effect on purchase intention. e-WOM has a positive and significant effect on brand image. Brand image significantly mediates the effect of e-WOM on purchase intention. The implication of this research is that Fore Coffee needs to pay better attention to the e-WOM aspect of purchase intention. e-WOM and brand image can be improved by providing online discussion forums, promotions, and content marketing that make it easier for potential customers to recognize and attract purchase intention for Fore Coffee products.